Antilipase and antioxidant activity of Orthosiphon stamineus methanolic extract - Alias, Norsyuhada; Thean Chor, Adam Leow; Mohamad Ali, Mohd. Shukuri; Salleh, Abu Bakar; Tajudin, Asilah Ahmad; Raja Abd. Rahman, Raja Noor Zaliha (IIUM Medical Journal Malaysia, 2016)
Introduction: Antilipase from natural resources are a potential tool for the treatment of obesity while antioxidant-rich plants are essential in combating degenerative diseases. The aim of this study is to determine the antilipase and antioxidant activity of Orthosiphon stamineus methanolic extract. Methods: The inhibitory activity against pancreatic lipase was determined by measuring the hydrolysis of p-nitrophenyl butyrate to p-nitrophenol at 405 nm. Antioxidant activity of O. stamineus extract was measured by 2, 2, diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity assay. Results: The O. stamineus crude extract exhibited strong lipase inhibitory activity with an IC50 value of 34.7 µg/ml. The inhibition mode study disclosed that O. stamineus could act as uncompetitive inhibitor. O. stamineus showed high antioxidant activity with an EC50 value of 26.3 µg/ml. Conclusions: The results suggest that O. stamineus has shown potential as a source of natural antilipase and antioxidant.